Up-regulated serum lactate dehydrogenase could become a poor prognostic marker in patients with bladder cancer by an evidence-based analysis of 2,182 patients - Wei, Xiaoyu; Chai, Yumeng; Li, Zhouyue; Che, Xuanyan; Zhang, Yong; Zhou, Zhongbao; Wang, Xiang (Frontiers in Oncology, 2023)
Background: A growing number of studies have considered serum lactate dehydrogenase (LDH) as an indicator of bladder cancer (BC) prognosis. However, a meta-analysis of the serum LDH's influence on BC prognosis is still missing.Methods: PubMed, EMBASE, Web of Science and Cochrane Library were exhaustively searched for studies comparing oncological outcomes between high-LDH and low-LDH patients. Standard cumulative analyses using hazard ratios (HR) with 95% confidence intervals (CI) were performed using Review Manager (version 5.3) for overall survival (OS) in patients with BC.Results: Six studies involving 2,182 patients were selected according to predefined eligibility criteria. The results showed that serum LDH level was significantly associated with OS (HR = 1.86, 95%CI = 1.54-2.25, p＜0.0001) in BC. Sensitivity analysis showed the stability of the results. Subgroup analysis revealed that the levels of serum LDH had a significant impact on the OS of BC patients among different groups including publication time, research country, sample size, tumor stage, LDH cut-off value, therapy and follow-up time (all HR＞1 and p＜ 0.05), revealing that the ability of serum LDH is not affected by other factors.Our findings indicated that a high level of serum LDH was associated with inferior OS in patients with BC. However, caution must be taken before recommendations are given because this interpretation is based upon very few clinical studies and a small sample.